Compared exergy analysis of sugarcane bagasse sequential hydrolysis and fermentation and simultaneous saccharification and fermentation. (2016) - Ortiz, Pablo Silva; de Oliveira, Silvio
This paper presents the compared exergy analysis of the enzymatic hydrolysis of sugarcane bagasse through Sequential Hydrolysis and Fermentation-SHF and Simultaneous Saccharification and Fermentation-SSF configurations to obtain lignocellulosic ethanol. Four pre-treatment processes were considered: Steam Explosion-SE, Organosolv, Liquid Hot Water-LHW, and a combined SE and LHW method. The pre-treatments analysed simultaneously with the SHF (Cases 1, 3, 5 and 7) and SSF (Cases 2, 4, 6 and 8) configurations were carried out for the overall system focus on the wine production. Processes simulations were performed by using Aspen Plus ® to a plant with 500 t/h milling capacity. The results for SHF configurations in terms of exergy efficiency rate were 60.0% for case 1, 56.5% for case 3, 58.3% for case 5 and 59.4% for case 7. For SSF configurations, the exergy efficiency obtained in case 2, case 4, case 6 and case 8 were 62.4%, 58.3%, 60.3% and 61.5%, respectively.